An Analysis of Public Opinion as Presented on News Networks’ Pages on Facebook: Kony 2012 Campaign - Al Balushi, Houda (Auckland University of Technology, 2013)
This thesis is an examination and exploration of the factors affecting the formation of public opinion during the Kony 2012 campaign. This research analyses an American-based campaign aimed at raising awareness of the issue of Ugandan child soldiers, even though the latter has not been an issue for the last six years. The campaign, which started in March 2012, sparked considerable controversy among politicians, socialists, economists and the general public in attempt to frame the issue. This work takes the stance that the global community is involved in and exposed to unlimited sources of knowledge for building their own counter-frames, and that the development of public opinion can be tracked through the exploration of cable news networks’ pages on Facebook. A critical discourse analysis (CDA) has been used in this research as a methodological framework due to its flexibility as a research method, as well as applying elements of content analysis and intertextual analysis. Due to CDA’s critical nature, insights can be given into why changes take place, and thus interpreting them is rendered possible. Content analysis of 16 posts by four cable news networks and 1,000 comments by audiences was conducted to examine how the subjective tone of coverage by news networks, the public, and their social networks affected the formation of public opinion. In order to gauge the impact of these factors, the researcher measured opinions that the public expressed by comparing them to the posted news by each news network separately. Several tables, graphs, and images have been employed to draw a picture of how public opinion developed over a period of two weeks. The key findings of this study show how the framed news can affect how the public perceives events by making some issues more salient than others. Moreover, the audiences’ identities and their social networks, or on the online public sphere, affect the perception of framed news and consequently, public opinion; both factors affect each other. It was also found that the manner in which these factors affect each other cannot be predicted because the latter is dependent on other variables that cannot be controlled, including individuals’ preferences and interests, identity, culture, ideology, values, beliefs or frames of references in general. Most important, however, is the finding that online public opinion is not independent of offline public opinion: they interact, which is further proof that the hypodermic needle effect of news is overrated and outdated. News media are influenced as much by public opinion as they influence it.
Keywords: Public opinion; Cable news networks; Facebook; Campaign; CDA; Framing